Nilai Tekanan Pengembangan Tanah Ekspansif Ketika Menerima Beban Dan Tanpa Menerima Beban Slab - Cahyo Agung Saputra; Fahira Rhomianti Putri (Program Studi Teknik Sipil Universitas Wiralodra, 2023)
Expansive soil is a soil that easily shrinks and expands. so that it often causes problems for civil building construction, for example causing road construction to experience damage to cracks, waves, and potholes. holes. This soil has the following characteristics large shrinkage expansion due to changes in pore volume that can cause a lifting force to the existing construction existing construction so that it can cause damage to the construction. The purpose of this research is to find out how muchvalue of the swelling pressure that occurs when expansive soil is in a loaded and unloaded state.state and without load. This research is the result of combining two studies that are summarized into one. summarized into one, so as to obtain a more in-depth analysis. The form of this research is experiment with the material used expansive soil taken from Sambungmacan, Sragen, Central Java. Central Java. Test equipment main test equipment used in this test is in the form of test box made of steel. The soil expansive soil is then compacted inside the test box. Then expansive soil is then gradually little by little moistened with water until it reaches maximum water content to determine the swelling pressure that occurs. The results showed that the value of the swelling pressure values that occur have fluctuating values